Development of Physics Teaching Materials of Optical Devices Based on Learning Assisted Guided Inquiry Crossed Puzzles (Department of Physics, Faculty of Mathematics and Natural Sciences, 2019)
This research aims to produce the teaching materials based on the inquiry learning model with valid, effective, and practical crossword puzzle of a physics lesson, especially in the optical appliance material of junior high school. The type of this research is developmental research using a 4 D model. The 4-D model consists of 4 stages of defining, designing, developing, and distributing. This research uses the development model. The methodology used is quantitative descriptive. Likert scale is used in this research as the validity analysis. Furthermore, the practical analysis is achieved from observation instrumental of lesson plan implementation, which written in the observation sheet, and student and teacher response questionnaire.Â The result of the research showed that the validity analysis of teaching material is valid. Moreover, the result of lesson plan implementation, teacher response questionnaire, student response questionnaire, categorized to very practical. The findings of this research showed that inquiry learning with a crossword puzzle in optical appliance material was very valid, practical, and useful.